Problems in Determining and Affirming Village Administrative Boundaries - Sary, Desy Puspita; Auliasari, Auliasari; Sari, Yeny Nurita; Rizani, Rahmadini Mutiara; Santoso, Lukman; Roi’fah, Nisfathur (NEGREI: Academic Journal of Law and Governance, 2023)
Research related to the problems of village boundaries still needs to be conducted because there are still many disputes over village boundaries. This research focuses on the problematic determination and affirmation of village boundaries in the Governance and Cooperation Section of the Regional Secretariat of Ponorogo Regency. This research aims to determine the juridical basis for determining and affirming village administrative boundaries and the problems of determining and affirming village administrative boundaries in the Governance and Cooperation Section of the Regional Secretariat of Ponorogo Regency. The research method used in this research is the normative juridical research method using descriptive data analysis and library and interview data collection methods. From this research, results were obtained, including: a) Laying boundary pillars; b) Measurement equipment must use tools, but they are not owned by the Governance and Cooperation Section of the Regional Secretariat of Ponorogo Regency; c) Personnel, there are no application processors, and boundary analysts so it is difficult to carry out the determination and affirmation of village boundaries; d) Insufficient budget hampers the process of determining and affirming village boundaries; e) Human Resources, and f) Related to the determination and affirmation process problems are starting from delineation to technical verification.